Execution in the concept of psychological anthropology - Baki, Samir; Mustafa, Majid (Al-Adab Journal, 2024)
The community of death row forms a parallel universe to the prison society within the Iraqi correctional institution, which in turn constitutes a world and a society parallel to the society in which you live. This narrow world with its space and freedom contains many conflicts, hopes and fear, the anxiety of waiting for the next, it is an important station of the next stations for the prisoners who live in it, waiting for death is one of the most difficult moments that an individual can live, and there is no doubt that this waiting is clearly reflected in the daily life of the waiting inmates, especially in terms of their food, behavior, dreams, expectations, health condition, long-term relationships and ambitions that they want to reach, and there is no doubt that prison is a special culture However, it is not completely separated from the mother culture from which the inmate branchs, which came from her world uttered his criminal act, as the study concluded according to the theory of the world Goffman as well as Freud that the process of interaction that occurs inside the prison and the process of stigma and the processes of institutional dealings and the death of the subjects, as well as the duality in dealing and the anomaly that exists despite reaching the stage of death, all give a foundational model for the work of both the daily life of those sentenced to death and the prison institution charged with the work of that private world. It is decreed for him and he acts according to what has been prepared for him from institutional roles that he does not know that it was prepared, not the death of himself, and the industry of another institutional self is more submissive.